The bond agio premium - Jochen Güntner; Benjamin Karner (Johannes Kepler University of Linz, Department of Economics, 2023)
Bonds issued in high and low interest-rate environments often list at different prices despite very similar characteristics. From a risk-neutral investor's perspective, higher current prices imply higher losses in case of default, which must be compensated, if markets are efficient. We call this the "bond agio premium" and use constituent-level bond index data for January 1997 through December 2022 to show that - holding issuer and maturity fixed - it is reflected by bond prices. Higher premia for lower rating buckets imply that different estimates for US dollar- and euro-denominated bonds are consistent with different fractions of sovereign and corporate debt.
Keywords: G11; G12; G14; G33; 330; Bond agio premium; Bond pricing; Empirical asset pricing; Fixed income factor investing